Use of Leaves of Cauliflower for the Removal of Iron from Waste Water - Farooqui, Mazahar; Kotharar, Sandeep; Zaheer, Ahmed; Ubale, Sanjay (Asian Journal of Chemistry, 2010)
The paper describes the use of modified powder of leaves of cauliflower for the removal of iron from industrial waste water. The presence of heavy metals is toxic even in trace quantities. In the present study we used leaves of cauliflower for the binding of Fe2+ ions. The removal of Fe2+ is efficient at pH 1 temperature 25ºC